Analisis Kemampuan Berpikir Kritis pada Siswa Kelas X MIPA 4 SMA Shalom Bengkayang - Dewi Tila Elisa; Pebria Dheni Purnasari; Siprianus Siprianus (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2022)
This study aims to determine the critical thinking ability of the tenth graders of SMA Shalom, Bengkayang city in the 2021/2022 academic year. The number of respondents in this study was 22 students, with data collection methods in the form of test questions for students' understanding of the power and energy material in physics lessons with aspects of the assessment of formulating data, analyzing data, comparing data, understanding material concepts, knowing material concepts, instruments in the form of questions. From the 5 aspects of the assessment, it turns out that the results are quite diverse. In the aspect of problem formulation, the dominant value is 4 with a percentage of 80%. while the data analysis aspect of the students' answers showed a dominant score of 4 with a percentage of 65%. Aspects of comparing, students are more dominant in getting a score of 4 with a percentage of 85%. In addition to the aspect of understanding the concept, the dominant student gets a score of 2 with a percentage of 75%, and the aspect of knowing the concept, the answer of the dominant student gets a score of 4 with a percentage of 80%.